EL1 and EL2 doctoral students' experience in writing the discussion section: A needs analysis. Issue 40 (July 2019) - Shen, Lifen; Carter, Susan; Zhang, Lawrence Jun
Abstract: This article reports on a micro-level needs analysis of thesis discussion writing. An anonymised digital survey collected information from 295 doctoral candidates about their self-defined learning needs for thesis discussion writing. Participant variables include English language background (English First Language (EL1) speakers and English as an Additional or Second Language (EL2) speakers), discipline (Hard pure & Soft pure, Engineering, and Education), writing stage (early, mid, and final), and type of research methods (experiments, case studies, simulations, etc.). Findings reveal significant differences in students' perceptions of challenges and the genre conventions along these factors. The analysis also shows students' high expectations for the specificity and depth of support that they would like. Theoretically, the findings add to what is known about the challenges in EL1 and EL2 doctoral discussion writing. Pedagogically, they offer insights for supervisors and future students. We conclude the paper with some implications for future study into the teaching of thesis writing and doctoral supervision.